Polarisation response of delay dependent absorption modulation in strong field dressed helium atoms probed near threshold. (12th August 2016) - Simpson, E R; Sanchez-Gonzalez, A; Austin, D R; Diveki, Z; Hutchinson, S E E; Siegel, T; Ruberti, M; Averbukh, V; Miseikis, L; Strüber, C S; Chipperfield, L; Marangos, J P
Abstract: We present the first measurement of the vectorial response of strongly dressed helium atoms probed by an attosecond pulse train (APT) polarised either parallel or perpendicular to the dressing field polarisation. The transient absorption is probed as a function of delay between the APT and the linearly polarised 800 nm field of peak intensity 1.3 × 10 14 W cm − 2 . The APT spans the photon energy range 16–42 eV, covering the first ionisation energy of helium (24.59 eV). With parallel polarised dressing and probing fields, we observe modulations with periods of one half and one quarter of the dressing field period. When the polarisation of the dressing field is altered from parallel to perpendicular with respect to the APT polarisation we observe a large suppression in the modulation depth of the above ionisation threshold absorption. In addition to this we present the intensity dependence of the harmonic modulation depth as a function of delay between the dressing and probe fields, with dressing field peak intensities ranging from 2 × 10 12 to 2 × 10 14 W cm − 2 . We compare our experimental results with a full-dimensional solution of the single-atom time-dependent (TD) Schrödinger equation obtained using the recently developed abinitio TD B-spline ADC method and find good qualitative agreement for the above threshold harmonics.